Prevalence of temporomandibular disorders and bruxism in Uruguay. Part I (Odontoestomatología, 2018)
Objectives: To determine the prevalence of bruxism and TMD in two populations in Uruguay: the capital city, Montevideo, and outside Montevideo. Method: A cross-sectional study was conducted throughout the country with stratified multistage sampling. Results: The variables selected and analyzed in this first paper were: degree of mouth opening, muscle pain, TMJ clicking, parafunctional wear facets, headache, history of joint noise, feeling of clenching during sleep and self-perception of stress. The following global prevalence rates were found: TMD: 55%, with at least one symptom, it being more prevalent in Montevideo (57%) than outside Montevideo (53%); with at least one sign: 44%, it also being more prevalent in Montevideo (47%) than outside Montevideo (41%). As for active bruxism, regarding the feeling of clenching during sleep, a prevalence of 30.72% was found in Montevideo and 23.19% outside Montevideo, while being or having been a bruxer in the assessment of the parafunctional wear facets had a prevalence of 71.95% in Montevideo and 62.17% outside Montevideo. Conclusions: With this survey, we found a high prevalence of TMD and bruxism in the Uruguayan population and encourage the development of collective prevention and treatment actions.